Highlights in gibberellin research: A tale of the dwarf and the slender - Shani, Eilon; Hedden, Peter; Sun, Tai-Ping (Plant physiology, 2024)
It has been almost a century since biologically active gibberellin (GA) was isolated. Here, we give a historical overview of the early efforts in establishing the GA biosynthesis and catabolism pathway, characterizing the enzymes for GA metabolism, and elucidating their corresponding genes. We then highlight more recent studies that have identified the GA receptors and early GA signaling components (DELLA repressors and F-box activators), determined the molecular mechanism of DELLA-mediated transcription reprograming, and revealed how DELLAs integrate multiple signaling pathways to regulate plant vegetative and reproductive development in response to internal and external cues. Finally, we discuss the GA transporters and their roles in GA-mediated plant development.
Keywords: Gibberellins; Plant Development; Plant Proteins; Gene Expression Regulation, Plant; Plant Growth Regulators; Signal Transduction; regulace genové exprese u rostlin; gibereliny; regulátory růstu rostlin; rostlinné proteiny; signální transdukce; vývoj rostlin